Adolescent Health and Well-Being: Background and Methodology for Review of Potential Interventions - Salam, Rehana A.; Das, Jai K.; Lassi, Zohra S.; Bhutta, Zulfiqar A. (Journal of adolescent health, 2016)
Owing to child survival initiatives around the world in the 1970s and 1980s, a dramatic rise in the population of adolescents has been seen, especially in the developing countries. A quarter of world's population in 2012 comprised adolescents and young adults; of these, 90% lived in low- and middle-income countries. More recently, there has been a consensus on investing in adolescent health and development for the success of post-2015 developmental agenda. In this series of articles, we aimed to assess various interventions identified in our conceptual framework to evaluate their effectiveness in improving adolescent health. We took a systematic approach to consolidate the existing evidence. This article is an introductory article detailing the background, conceptual framework, and methodology used for synthesizing evidence, followed by seven articles summarizing evidence on interventions for sexual/reproductive health, nutrition, immunization, mental health, substance abuse, and accidents/injury. The concluding article of the series summarizes the findings of the all the previous articles in the series and the relevance of the evidence for action in the post-2015 Millennium Development Goals era along with evidence gaps and future research priorities.